Cyclic Behavior of Confined Cement-Stabilized Rammed Earth Walls - Xinlei Yang; Hailiang Wang; Ziliang Zhao (Shock and Vibration)
Rammed earth is widely utilized in both developed and developing countries due to its low embodied energy and good natural moisture buffering of indoor environments. However, its application in seismic active regions was limited owing to its intrinsically low resistance to dynamic actions. This paper presents the test results of four cement-stabilized rammed earth walls with confining tie-column elements under cyclic loading, aiming at assessing the cyclic behavior of proposed rammed earth walls with confining tie-column elements. The test results revealed that the proposed confining tie-column elements could significantly improve the cyclic behavior of cement-stabilized rammed earth wall, exhibiting good strength and ductility.